A aquisição de significados em música: transferência de função de valência de expressões faciais de emoções para trechos musicais - Ribeiro, Jéssica (2024)
Experimental aesthetics encompasses diverse lines of research that primarily explore how structural characteristics of music influence aesthetic experience. The Stimulus Equivalence Paradigm offers tools to address a distinct research problem that diverges from the traditional focus in this field: is it possible for aesthetic stimuli to acquire meaning through conventions established by a verbal community, based on arbitrary criteria? To begin investigating this question, we conducted two experiments in which we programmed equivalence relations between facial expressions and musical excerpts, without presenting these stimuli simultaneously or contiguously. We evaluated the influence of relational training on the valence attributed to the music, using a Semantic Differential. In Experiment 1, 12 out of 16 participants met the criterion for the equivalence test. For these participants, we observed a reduction in the valence attributed to musical excerpts equivalent to sad facial expressions (statistically significant) and an increase in the valence of excerpts associated with happy facial expressions (although this difference was not statistically significant). Replicating the results of the first experiment, in Experiment 2, equivalences were established for 9 out of 20 participants. We noted a statistically significant decrease in the valence of the musical excerpt equivalent to expressions of disgust, and a marginally significant increase in the valence of the musical excerpt equivalent to happy facial expressions. The results indicate the occurrence of transfer of function between stimuli, supporting the initial hypothesis that musical stimuli can acquire meanings through the conventions of a verbal community.